2018
DOI: 10.1007/s11205-018-1993-1
|View full text |Cite|
|
Sign up to set email alerts
|

Beyond Formal Access: Organizational Context, Working From Home, and Work–Family Conflict of Men and Women in European Workplaces

Abstract: Working from home has become engraved in modern working life. Although advocated as a solution to combine work with family life, surprisingly little empirical evidence supports that it decreases work-family conflict. In this paper we examine the role of a supportive organizational context in making working from home facilitate the combination of work and family. Specifically, we address to what extent perceptions of managerial support, ideal worker culture, as well as the number of colleagues working from home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 74 publications
5
97
0
7
Order By: Relevance
“…Previous research indicates that women often perceive lower WLB than men [56], and our results confirm that for office workers with flexible work arrangements. However, we found that gender rarely had an effect on associations between occupational or individual factors and WLB.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous research indicates that women often perceive lower WLB than men [56], and our results confirm that for office workers with flexible work arrangements. However, we found that gender rarely had an effect on associations between occupational or individual factors and WLB.…”
Section: Discussionsupporting
confidence: 89%
“…Since WLB may be experienced differently by men and women, and gender may modify associations between working conditions and WLB [55,56], we performed a sensitivity analysis by re-running the regression models above including two-way (factor x gender) and three-way (factor x flexible work x gender) interactions. We examined statistically significant interactions (p < 0.05) further, using gender-stratified analyses.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…There is an abundance of studies on the impact of HBW on WLB (see e.g. Aguilera et al 2016;Morganson et al 2009;Maruyama et al 2009;Hilbrecht et al 2008;Hislop and Axtell 2007;Crosbie and Moore 2004;Sullivan and Lewis 2001;Lott 2018;van der Lippe and Lippényi 2018;Kim 2018;Chung and Van der Lippe 2018). In some of these studies, HBW is implicitly, and sometimes explicitly (Felstead et al 2002; see also Gregory and Milner 2009) conceptualized as a work-life balance practice.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…enabling multitasking), thus increasing tensions between work and family schedules (e.g. ; Hartig et al 2007;Marsh and Musson 2008;Russell et al 2009;Sullivan and Lewis 2001;van der Lippe and Lippényi 2018). Furthermore, it increases the amount of time women, in contrast to men, spend on housework and childcare, thereby strengthening/reproducing gender roles (Sullivan and Lewis 2001;Hilbrecht et al 2008;Kim 2018;Chung and Van der Lippe 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, whether employees benefit from telework is controversial. Besides work-home conflict (Van der Lippe & Lippényi, 2018) and mental health problems (Mann & Holdsworth, 2003), some studies (Glass & Noonan, 2016;Martinez & Gomez, 2013) have shown that telework is related to negative career consequences, whereas other studies (Riley & McCloskey, 1996;Tolbert & Simons, 1994) have found no support for telework being harmful to careers.…”
Section: Introductionmentioning
confidence: 99%